2013
DOI: 10.1007/s12639-013-0252-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activity of certain medicinal plants against chloroquine resistant Plasmodium berghei infected white albino BALB/c mice

Abstract: In the present study of antimalarial efficacy, aqueous extracts of leaves and unripe fruits of Psidium guajava, leaves of Ocimum sanctum and leaves of Murraya koenigii are evaluated against Plasmodium berghei (chloroquine resistant NK65 strain) infected white albino BALB/c mice. A 7 days oral administration was adopted with different dosage viz., 350 mg, 750 mg and 1,000 mg/kg body weight as treatment schedule along with parasite (Group I) and drug control with Chloroquine, 50 mg/kg body weight (Group II). All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…This problem is observed during the long-term treatment of malaria (Lacrue et al, 2011). Moreover, similar antiplasmodial studies suggested that follow-up of mice for at least 1 month becomes necessary in order to monitor the efficacy of any antimalarial drug (Rajendran et al, 2014). Thus, all mice were observed for their mean survival time period in the present study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This problem is observed during the long-term treatment of malaria (Lacrue et al, 2011). Moreover, similar antiplasmodial studies suggested that follow-up of mice for at least 1 month becomes necessary in order to monitor the efficacy of any antimalarial drug (Rajendran et al, 2014). Thus, all mice were observed for their mean survival time period in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…A dose of 350 mg/kg/body weight showed 53.9% chemosuppression. A similar in vivo study revealed that various crude extracts obtained from Psidium guajava, Ocimum sanctum, and Murraya koenigii showed antiplasmodial activity against P. berghei infected albino mice with various higher doses namely 350, 750, and 1000 mg/kg, p.o., bw for 7 d (Rajendran et al, 2014). Herein, the in vivo activity of AREBA was recommended to be strong as previous studies, as the lower dose, i.e., 350 mg/kg bw exerted suppressive activity by 53.9% (Figure 3).…”
Section: Discussionmentioning
confidence: 88%
“…The leaves also showed anti-malarial effect in BALB/c mice infected with Plasmodium berghei via parasitemia suppression [99]. Moreover, guava leaves are also recommended for treating infectious diarrhea since they prevented intestinal colonization of Citrobacter rodentium in Swiss albino mice [100].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Recently, promising in vitro antiplasmodial activity against 3D7 (IC 50 ≤ 20 μg/ml), was seen in leaves ethyl acetate extracts and methanol extracts of Pg (Kaushik et al, 2015) and synergistic activities of combination with ethanol and water macerations of Mangifera indica, Carica papaya, Cymbopogon citratus, Citrus sinensis, and Ocimum gratissimum were reported against P. falciparum 3D7 and Dd2 strains (Tarkang et al, 2014). Aqueous decoctions of Pg also showed anti-plasmodial activity against chloroquine resistant P. berghei (Rajendran et al, 2014).…”
Section: Samplementioning
confidence: 99%
“…Maceration, infusion or decoction in water of different parts of P. guajava are used in several countries as febrifuge or in skin problems (Gutiérrez et al, 2008;Hermans et al, 2004;Ajaiyeoba et al, 2003). Aqueous decoctions and various extracts from leaves and flowers of P. guajava, alone or in combination with other medicinal plant extracts possess in vitro anti-plasmodial activities (Kaushik et al, 2015;Tarkang et al 2014;Rajendran et al, 2014;Chinchilla, et al, 2012). E. camaldulensis leaves are used alone and in combination with other plants to treat malaria and typhoid fevers in some Northern parts of Nigeria and ethanolic extracts possess in vivo anti-trypanosomal activities (Kabiru et al, 2013).…”
Section: Introductionmentioning
confidence: 99%